INVESTASI RAJA SALMAN DI INDONESIA DALAM PANDANGAN EKONOMI MAKRO ISLAM - Ardiani, Ninda Ardiani (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The purpose of this research is to look at the investment that King Salman has made in Indonesia in view of the macro-Islamic economy. Involvement of foreign parties here provides additional existing capital, lowers existing unemployment, improves development, increases selling products value in the country and the establishment of multiteral or bilateral cooperation. Foreign investment made by Saudi Arabia during 2016 is in position 57 of 121 existing Country. The investment made by Saudi Arabia is 0.9 USD and involves 44 Projects. The results of this study indicate that the granting of Saudi Arabia Investment to Indonesia in order to visit the king of salman to Indonesia gave a positive impact that is approved by the cooperation of oil refinery in cilacap. Investments in Islamic Economy Countries are underpinned by Three Factors, namely (1) there are sanctions against the less or unproductive holder (hoarding idle assets); (2) prohibited from any form of speculation and all kinds of gambling; (3) the interest rate of various loans is zero